The Translation of Cultural Words in Folk Tale “The Origin of the Word Babah” on the Google Translate Service - Mohammad Siddiq; Ahmad Juma Khatib Nur Ali; Taufiq Effendi (LADU: Journal of Languages and Education, 2023)
Background: Folk tale contains words that are bound to a certain cultural context. Globalization and technological developments have made wider access to the folk tales. Google Translate is a translation service that can help translate folk tales with a wide range of users. Purpose: The focus of this research is limited to how the Google Translate service translates the cultural words in the folk tale of The Origin of the Word Babah. Design and methods: This research method is descriptive qualitative with research data on the cultural words in the folk tale The Origins of the word Babah which is published by the Ministry of Education and Culture in 1978. This study used analysis of translation strategies and Newmark’s Cultural Words categories as referred classification. Results: The result of the study shows that the 10 (ten) research data are all in the category of social customs. The translation strategies used are Loan with 5 (five) data and Literal Translation with 5 (five) data. This research shows that Google Translate has not been able to detect cultural contexts, hence it is not accurate in translating cultural addresses and special terms.